2017
DOI: 10.1007/s10443-017-9642-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Modelling of the In-Plane Reinforcement Orientation Variations in a CFRP Laminate Produced by Manual Lay-Up

Abstract: and modelling of the in-plane reinforcement orientation variations in a CFRP laminate produced by manual lay-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Davilla et al 5 implemented an image analysis technique using Hough lines to determine the ply orientation from images taken of the laminate at each stage of the layup. They presented an approach that was able to achieve the mean ply orientations to within ±0.5° with standard deviations ranging between 0.34° and 0.41°, but this approach is not applicable for quantifying the orientation of a part after it has been manufactured as it can only be used for the outer most lamina 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davilla et al 5 implemented an image analysis technique using Hough lines to determine the ply orientation from images taken of the laminate at each stage of the layup. They presented an approach that was able to achieve the mean ply orientations to within ±0.5° with standard deviations ranging between 0.34° and 0.41°, but this approach is not applicable for quantifying the orientation of a part after it has been manufactured as it can only be used for the outer most lamina 5 …”
Section: Introductionmentioning
confidence: 99%
“…They presented an approach that was able to achieve the mean ply orientations to within AE0:5 with standard deviations ranging between 0:34 and 0:41 , but this approach is not applicable for quantifying the orientation of a part after it has been manufactured as it can only be used for the outer most lamina. 5 Ultrasound has been used by multiple researchers for laminated composites. For example, Hsu et al 6 used a vector decomposition method whereby an image of a correctly fabricated part was aligned against an unknown part, and they were able to identify the ply misorientation and layup symmetry.…”
mentioning
confidence: 99%
“…Alternatively, simple camera systems and image filtering techniques have been used to determine fibre misalignment across the surface of large unidirectional prepreg plies, prior to composite layup and consolidation. 11 This work relied on the edge detection of individual fibres or bundles at high resolution in smaller subset areas to calculate the local mean fibre orientation. A similar method taking images of subset areas (75 × 75 mm 2 ) under diffuse lighting conditions has been used to evaluate the fibre distribution in glass fibre SMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative camera-based systems to measure fibre orientations have also been developed for various purposes with some success. [23][24][25] However, previous research by the authors has demonstrated a fibre orientation measurement technique based on optical reflectance that can be performed quickly across very large surfaces at a low cost. 26 As an extension of this approach, the current work improves its reliability and applies the technique to the evaluation of flow-induced fibre alignment in panels manufactured from high flow charges, presented in Experimental testing.…”
Section: Fibre Orientation Analysismentioning
confidence: 99%
“…Alternative camera-based systems to measure fibre orientations have also been developed for various purposes with some success. 2325 However, previous research by the authors has demonstrated a fibre orientation measurement technique based on optical reflectance that can be performed quickly across very large surfaces at a low cost. 26…”
Section: Introductionmentioning
confidence: 99%